LOW-TEMPERATURE MICELLAR EXTRACTION FOR THE CONCENTRATION OF BIOMOLECULES: UDC 543.2, 542.61, 611.185.1 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The influence of nature and concentration of the nonionic surfactants, acidity and introduction of different additives on parameter of the phase separation at the cloud point temperature was investigated. The possibility of the extraction of albumin into micellar-rich phases of the nonionic surfactants was shown. The nature of surfactants and the acidity of the medium are the base factors for the regulation of the micelle extraction processes was indicated.
Keywords: -